Eicosanoids in human heart failure: pilot study of plasma epoxyeicosatrienoic and dihydroxyeicosatrienoic acid levels - Kala, Petr; Hnat, Tomas; Padrova, Karolina; Kotaška, Karel; Veselka, Josef (Archives of medical science, 2023)
INTRODUCTION: The role of eicosanoids, metabolites of arachidonic acid with cardio-renal activity, remains unclear in human heart failure (HF). METHODS: We enrolled 50 patients with HF to measure plasma 14,15-EET and 14,15-DHET levels using commercial ELISA kits and compared them with 25 age- and sex-matched controls. RESULTS: Both of the measured eicosanoids were significantly higher in the HF group: 14,15-EET (91.3 ±25.7 ng/ml vs. 64.95 ±35.4 ng/ml) and 14,15-DHET (10.58 ±2.06 ng/ml vs. 9.07 ±1.60 ng/ml), p for both < 0.001. CONCLUSIONS: We found that peripheral plasma eicosanoid (14,15-EET, 14,15-DHET) levels are raised in patients with HF compared to age- and sex-matched controls.
Keywords: eicosanoids; heart failure; epoxyeicosatrienoic acid; dihydroxyeicosatrienoic acid